Late Wisconsinan Glacial Geomorphology of the Kent Interlobate Complex, Ohio, USA - Santos, João Bessa (2012)
The northern sector of the Kent Interlobate Complex, created by twomajor ice lobes of the Laurentide Ice Sheet during late Wisconsinan times, dominates theglacial landscape of northeast Ohio. The geomorphology of this impressive complex revealsthe presence of large hummocks, kettle lakes and substantial esker chains. The esker chains,usually smaller than 1.3 km long, run parallel to the interlobate complex geographicorientation of northeast-southwest. Gravel pits present on large hummocks display beddedand sorted sedimentary units of gravel, sand and gravel and climbing ripple laminated sandwith folds, which demonstrate that the northern sector of the interlobate complex isprimarily a glaciofluvial feature. Topping these hummocks is a massive clast-supporteddiamicton interpreted to be a debris flow. These geomorphic and sedimentary characteristicsseem to indicate that hummocks present in the interlobate area are in fact kames and that theentire northern sector of the interlobate complex is a product of late Wisconsinan timetransgressive ice stagnation that occurred between two major ice lobes.